Historical considerations regarding the first descriptions of pancreas’ anatomy - Paraskevas, George; Koutsouflianiotis, Konstantinos; Lazaridis, Nikolaos; Iliou, Kalliopi; Bitsis, Theodosios; Noussios, George; Syrmos, Nikolaos (Italian Journal of Anatomy and Embryology, 2019)
The descriptions of the term “pancreas” as well the macroscopic anatomy of the pancreas throughout Antiquity, Byzantium, Middle Ages and Renaissance are displayed. In particular, the original phrases of famous physicians of that period as regards the anatomy of the pancreas are presented: Hippocrates, Aristotle, Herophilus, Galen, Rufus of Efesus, Julius Pollux, Oribasius, Bartolomeo Eustachio, Andreas Vesalius, Gabriel Fallopius, Johann Georg Wirsung, Francis Glisson, Giovanni Domenico Santorini.